(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the postoperative analgesic outcomes of a multimodal analgesic regimen including continuous transversus abdominis plane (TAP) block in kidney transplant recipients at Military Hospital 175. Subjects and Methods: This prospective case series with longitudinal follow-up was conducted on 76 patients undergoing kidney transplantation at Military Hospital 175 from July 2023 to September 2025. Postoperatively, patients received a multimodal analgesic regimen consisting of continuous patient-controlled transversus abdominis plane (TAP) block, intravenous nefopam infusion, scheduled paracetamol and rescue morphine when required. Pain outcomes were assessed using the visual analogue scale (VAS) at extubation and at multiple time points within 72 hours postoperatively, along with PCA usage, time to first PCA demand, and other postoperative variables. Results: Among 76 patients (50 males and 26 females), the mean surgical duration was 127.7 ± 17.8 minutes, and the mean incision length was 12.5 ± 2.3 cm. Two hours after extubation, 98.7 % of patients had VAS < 4. On the first postoperative day, 91% reported mild pain (VAS < 4), while 7 patients (9%) experienced moderate pain (VAS 4–6 ). At subsequent time points, the proportion of patients with VAS < 4 remained high (>95%). The incidence of adverse effects was low. Conclusion: A multimodal analgesic regimen including continuous patient-controlled TAP block was associated with effective postoperative pain control after kidney transplantation, with reduced opioid requirements. Earlier return of gastrointestinal function, and a reduced risk of respiratory complications.